Biomarkers for the Clinical Diagnosis of Alzheimer’s Disease: Metabolomics Analysis of Brain Tissue and Blood - Wang, Yang-Yang; Sun, Yan-Ping; Luo, Yu-Meng; Peng, Dong-Hui; Li, Xiao; Yang, Bing-You; Wang, Qiu-Hong; Kuang, Hai-Xue (Frontiers in Pharmacology, 2021)
With the elder population rapidly increased in the world, age-related diseases such as Alzheimer’s disease (AD) have made global concern. Given that the drastic growth in the number of individuals rush growth and the irreversibility of the neurodegenerative disease represent a major emerging threat to public health. At present, there is still no clear cure for neurodegenerative disease, despite abundant substantial investments in medical institutions and scientific studies to alter the disease course. At the earliest clinical stages early to discover, detection, diagnosis were so key that modifying and intervention at potentially reversible stages. Therefore, there is an eager need for a biomarker that can facilitate diagnosis, classification, prognosis, and treatment response. At present, with the emergence of highly sensitive mass spectrometry platforms and high-throughput technology that are able to discover and catalog vast datasets of small metabolites, which respond to the changed status in the body. Metabolomics provides hope for a better understanding of AD and subsequent identification and analysis of metabolites. Here we reviewed the state of the art of emerging candidate biomarkers from recent literature to provide insights for the early diagnosis of AD in the future and discussed the changed metabolic network in the body.